The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.5194/bg-5-817-2008
|View full text |Cite
|
Sign up to set email alerts
|

Towards operational remote sensing of forest carbon balance across Northern Europe

Abstract: Abstract.Monthly averages of ecosystem respiration (ER), gross primary production (GPP) and net ecosystem exchange (NEE) over Scandinavian forest sites were estimated using regression models driven by air temperature (AT), absorbed photosynthetically active radiation (APAR) and vegetation indices. The models were constructed and evaluated using satellite data from Terra/MODIS and measured data collected at seven flux tower sites in northern Europe. Data used for model construction was excluded from the evaluat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 63 publications
1
36
1
Order By: Relevance
“…Recent efforts to link NDVI with ground‐based measurements of vegetation productivity have met with mixed success. In Scandinavia, mean monthly MODIS NDVI and flux tower GPP showed moderate correlations (r = 0.7–0.79) at seven forested sites; however, NDVI saturation during periods of high productivity (NDVI > 0.9) was a noticeable issue [ Olofsson et al , 2007]. At three flux tower sites located in Southeast Asian tropical forests, Huete et al [2008] found that the relationship between NDVI and gross ecosystem production varied considerably with forest type (r 2 = 0.00–0.53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent efforts to link NDVI with ground‐based measurements of vegetation productivity have met with mixed success. In Scandinavia, mean monthly MODIS NDVI and flux tower GPP showed moderate correlations (r = 0.7–0.79) at seven forested sites; however, NDVI saturation during periods of high productivity (NDVI > 0.9) was a noticeable issue [ Olofsson et al , 2007]. At three flux tower sites located in Southeast Asian tropical forests, Huete et al [2008] found that the relationship between NDVI and gross ecosystem production varied considerably with forest type (r 2 = 0.00–0.53).…”
Section: Discussionmentioning
confidence: 99%
“…At three flux tower sites located in Southeast Asian tropical forests, Huete et al [2008] found that the relationship between NDVI and gross ecosystem production varied considerably with forest type (r 2 = 0.00–0.53). Satellite vegetation indices, both NDVI and the enhanced vegetation index (EVI), show stronger associations with tower measurements in forests with seasonal, rather than evergreen, canopy cover [ Olofsson et al , 2007; Huete et al , 2008]. NDVI and EVI are related to productivity via light absorption, though differences in canopy phenology will affect the degree to which light absorption is biochemically decoupled from utilization for carbon assimilation [ Goetz and Prince , 1996].…”
Section: Discussionmentioning
confidence: 99%
“…Remote sensing variables, particularly vegetation indices, do not directly represent carbon fluxes processes (Jung et al, 2008), but as shown previously, they are statistically related to ecosystem fluxes (Olofsson et al, 2008;Rahman, Sims, Cordova, & El-Masri, 2005). Vegetation indices are calculated using measured reflectances in specific spectral bands that are related to some chemical and physical properties of the vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation indices are calculated using measured reflectances in specific spectral bands that are related to some chemical and physical properties of the vegetation. For example, greenness indices such as the Normalised Difference Vegetation Index (NDVI) or the Enhanced difference Vegetation Index (EVI) (Olofsson et al, 2008;Sims et al, 2008) are related to the amount of green biomass (e.g., leaf area index, LAI), whereas water indices such as the Normalised Difference Water Index (NDWI) (Gao, 1996) provide information on the canopy water content. Remote sensing data are also used as the basis to derive the land cover maps that are used in modelling exercises when the model parameterisation is specific for a Plant Functional Type (PFT).…”
Section: Introductionmentioning
confidence: 99%
“…The first type of studies proposed new models (different for LUEbased) to estimate GPP from remote sensing and showed how well the models estimated GPP (Olofsson et al, 2008;Sims et al, 2008;Schubert et al, 2012). Some of the models are simpler than the LUE approach and have been justified based on the claim that one or more parametrizations used in the LUE approach are not required (Gitelson et al, 2006;Sims et al, 2008;Jung et al, 2008;Jahan and Gan, 2009;Ueyama et al, 2010;Wu et al, 2011;Sjöström et al, 2011;Sakamoto et al, 2011;Hashimoto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%